Dynamic Evolution of Defect Structures during Spall Failure of Nanocrystalline Al. Issue 58 (10th March 2016) - Coleman, Kathleen; Agarwal, Garvit; Dongare, Avinash M.
ABSTRACT: The dynamic evolution and interaction of defects under the conditions of shock loading in nanocrystalline Al with an average grain size of 20 nm is investigated using molecular dynamics simulations for an impact velocity of 1 km/s. Four stages of defect evolution are identified during shock deformation and failure that correspond to the initial shock compression (I), the propagation of the compression wave (II), the propagation and interaction of the reflected tensile waves (III), and the nucleation, growth, and coalescence of voids (IV). The results suggest that the spall strength of the nanocrystalline Al system is attributed to a high density of Shockley partials and a slightly lower density of twinning partials (twins) in the material experiencing the peak tensile pressures.